2021
DOI: 10.3389/fpsyt.2021.770282
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin-Sensitive Magnetic Resonance Imaging in Schizophrenia: A Meta-Analysis of Case-Control Studies

Abstract: Background: Psychiatry is in urgent need of reliable biomarkers. Novel neuromelanin-sensitive magnetic resonance imaging (NM-MRI) sequences provide a time-efficient and non-invasive way to investigate the human brain in-vivo. This gives insight into the metabolites of dopaminergic signaling and may provide further evidence for potential dopaminergic alterations in patients with schizophrenia (SCZ). The present systematic review provides a meta-analysis of case-control studies using neuromelanin-sensitive seque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…(C) Neuromelanin MRI changes in schizophrenia. Schematic depiction of the consistent elevation of substantia nigra contrast-to-noise-ratio in patients with schizophrenia (SCZ) compared to healthy controls (HC), based on meta-analytic evidence ( 40 , 47 ).…”
Section: Distinct Magnetic Resonance Imaging-based Approaches For Stu...mentioning
confidence: 99%
See 2 more Smart Citations
“…(C) Neuromelanin MRI changes in schizophrenia. Schematic depiction of the consistent elevation of substantia nigra contrast-to-noise-ratio in patients with schizophrenia (SCZ) compared to healthy controls (HC), based on meta-analytic evidence ( 40 , 47 ).…”
Section: Distinct Magnetic Resonance Imaging-based Approaches For Stu...mentioning
confidence: 99%
“…A typical outcome measure of neuromelanin MRI analysis is the contrast-to-noise ratio (CNR), which describes the ratio between the signal in a presumably neuromelanin-rich region, for example substantia nigra, and the signal of a reference region that presumably contains no neuromelanin, for example crus cerebri ( Figure 2B ) ( 39 , 40 ). While neuromelanin MRI has been used to quantify dopaminergic neuron loss in neurodegenerative conditions for some time ( 39 , 41 , 42 ), it has recently also been validated to measure dopamine function in vivo in subjects without neurodegeneration: Cassidy et al showed a relationship between substantia nigra CNR and both post-mortem neuromelanin concentration in the substantia nigra and amphetamine-induced striatal dopamine release measured by PET ( 43 ).…”
Section: Distinct Magnetic Resonance Imaging-based Approaches For Stu...mentioning
confidence: 99%
See 1 more Smart Citation
“…While prior work indicates NM-MRI serves as a reliable proxy measure of the function of catecholamines (38) and shows promise as a clinical marker of disorders of these systems even in the absence of neurodegeneration, including depression and psychosis (64)(65)(66), the precise relationship to tonic (vs. phasic) dopamine remains unclear. Studies show chronic L-DOPA, which is thought to increase both phasic and tonic dopamine, increases neuromelanin concentration in both humans and rodents (66,67), providing some assurance that NM-MRI could serve as a reasonable proxy of these neurobiological processes.…”
Section: Exploratory Analyses Of Subregional Effects Confirm Specific...mentioning
confidence: 99%
“…[19][20][21]27 Therefore, age is a critical factor that should be adjusted for when using NM-MRI. 19,28 With these challenges in mind, future NM-MRI work using standard methods of acquisition and analysis and stratifying a large sample of participants by age would be well positioned to determine the normative range of SN and LC contrast ratios and volumes in healthy people of all ages. In the context of its potential use as a biomarker, access to a standardized, age-adjusted normative range of NM-MRI metrics is essential to identify patients on the extreme ends of the range, presumably those who may require clinical intervention.…”
Section: Introductionmentioning
confidence: 99%